Analisis Pengaruh Kinerja Keuangan Terhadap Kebijakan Dividen Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia - Chindy Valen Aryando Nasution; Noni Adrian (Journal of Research in Social Science and Humanities, 2025)
This study aims to analyze the effect of financial performance on the dividend policy of Commercial Banks listed on the IDX. The sample used in this study was 12 companies. The observation period used in this study was 5 years. The data obtained were analyzed using a statistical formula, namely by using panel data analysis which was processed using the eviews 12 program. The results of the partial analysis showed that the t-count value of 3.504 2.00 (t-table) and sig 0.0009 0.05, then H1 is accepted and H0 is rejected, it can be concluded that profitability has a significant effect on the dividend payout ratio of Commercial Banks listed on the IDX. The t-count value of 1.903 2.00 (t-table) and sig 0.0622 0.05, then H2 is rejected and H0 is accepted, it can be concluded that liquidity does not have a significant effect on the dividend payout ratio of Commercial Banks listed on the IDX. Solvency has a significant effect on the dividend payout ratio of Commercial Banks listed on the IDX. The calculated F value of 8.024 is greater than the F table of 3.16 with a significance level of 0.000 which is much smaller than 0.05, so it can be concluded that the H4 hypothesis is accepted, which means that profitability, liquidity and solvency have a significant effect simultaneously on the dividend payout ratio of Commercial Banks listed on the IDX